A Compendium of Pathophysiologic Basis of Etiologic Risk Factors for Painful Vaso-Occlusive Crisis in Sickle Cell Disease - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Sickle cell disease (SCD) is characterized by recurrent vaso-occlusive crisis (VOC). VOC is an important index of disease severity and has been shown to correlate with the risk of multi-organ damage and early death. Although the vulnerability to VOC among patients with SCD may be genetically predetermined on the basis of genotype and haplotype variability, nonetheless, VOC is usually triggered by a wide spectrum of etiologic risk factors, which range from physiological to nonphysiological factors on the one hand, and from psychological to physical factors on the other hand. An understanding of these risk factors and their pathophysiologic mechanisms is important for the hematologist to accurately identify potential etiologic risk factors for VOC. Thus taking preemptive action that will prevent undue exposure of patients to the risk factors and/or prepare the patient to uneventfully withstand the risk factors if exposure is unavoidable. This will ultimately obviate frequent VOC with its attendant risk of organ damage and early death in patients with SCD. Hence, in this study we conducted a broad and comprehensive review (using “sickle cell painful vaso-occlusive crisis” and relevant sub-terms in PubMed, Google Scholar, and other search engines) of various etiologic risk factors for VOC and the pathophysiologic mechanisms through which they trigger pain in patients with SCD.